KEPEMIMPINAN DALAM PENDIDIKAN ISLAM - Jailani Syahputra Siregar (Jurnal Al-Fatih, 2021)
In the context of Islamic education the leader has a strategic position. Leader as a skipper in determining where to go. Leadership in Islamic educational institutions is both a process and a key one. The role of the leader as the initiator in order to create cooperation among existing resources, in this case the process of influencing is the main task of a leader. The role of leadership in realizing superior education can be implemented through the accuracy given, the application of penalties and rewards to all stake holders, the commitment of leaders and the fulfillment of facilities and infrastructures or facilities that support the smooth process of Islamic education.